2011
DOI: 10.1074/mcp.m110.007492
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Proteomics Identifies a β-Catenin Network as an Element of the Signaling Response to Frizzled-8 Protein-Related Antiproliferative Factor

Abstract: Antiproliferative factor (APF), a Frizzled-8 protein-related sialoglycopeptide involved in the pathogenesis of interstitial cystitis, potently inhibits proliferation of normal urothelial cells as well as certain cancer cells. To elucidate the molecular mechanisms of the growth-inhibitory effect of APF, we performed stable isotope labeling by amino acids in cell culture analysis of T24 bladder cancer cells treated with and without APF. Among over 2000 proteins identified, 54 were significantly up-regulated and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 42 publications
1
37
1
Order By: Relevance
“…Three days after transfection, cell proliferation rate was determined by crystal violet staining. 59 Absorbance was measured at 570 nm.…”
Section: Methodsmentioning
confidence: 99%
“…Three days after transfection, cell proliferation rate was determined by crystal violet staining. 59 Absorbance was measured at 570 nm.…”
Section: Methodsmentioning
confidence: 99%
“…It was demonstrated that siRNA-mediated knockdown of CKAP4 specifically abrogates APF's effects on cell proliferation, MMP2/p53 protein expression, and Akt/GSK3β/β-catenin phosphorylation on T24 bladder carcinoma cells (75). The Akt/GSK3β/β-catenin signaling importance for APF signal transduction was not only demonstrated in T24 cells (HTB-4), but was also confirmed in an hTERT immortalized human bladder epithelial cell line, TRT-HU1 (75).…”
Section: Discussionmentioning
confidence: 91%
“…The APF cell inhibitory mechanism is the result of this small molecule binding to the membrane resident palmitoylated CKAP4 receptors causing inhibition of cell proliferation and alteration of the expression of genes relevant to cell-to-cell permeability (E-cadherin, vimentin, and tight junction protein, ZO-1) (74). It was demonstrated that siRNA-mediated knockdown of CKAP4 specifically abrogates APF's effects on cell proliferation, MMP2/p53 protein expression, and Akt/GSK3β/β-catenin phosphorylation on T24 bladder carcinoma cells (75). The Akt/GSK3β/β-catenin signaling importance for APF signal transduction was not only demonstrated in T24 cells (HTB-4), but was also confirmed in an hTERT immortalized human bladder epithelial cell line, TRT-HU1 (75).…”
Section: Discussionmentioning
confidence: 99%
“…Yue et al provided evidences that the proteins influenced in cancer cells by a purified G. lucidum component were searched globally using a proteomic technique and 21 proteins might be target-related proteins of ganoderic acid D [7]. In addition, it has been reported that beta-catenin was a key node of APF-regulated protein network in human bladder cells by a stable isotope labeling with amino acids in a cell culture (SILAC)-based quantitative proteomic approach combined with bioinformatic analyses [8].…”
Section: Introductionmentioning
confidence: 99%